Challenges in Minimally Invasive Choledochal Cyst Surgery - Revathy Menon; Kirtikumar J. Rathod; Taruna Yadav; Shubhalaxmi Nayak; Rahul Saxena; Avinash S. Jadhav; Manish Pathak; Arvind Sinha (Journal of Indian Association of Pediatric Surgeons)
Introduction: Choledochal cyst (CDC) is a rare congenital anomaly requiring surgical excision and bilioenteric reconstruction. Laparoscopic techniques have gained traction for their superior visualization, minimal postoperative pain, and cosmetic benefits. Materials and Methods: A retrospective review of 41 pediatric CDC excision and repair performed laparoscopically at a tertiary care center in India from July 2018 to February 2024 was conducted. Patient data included demographics, Todani classification, surgical technique, intraoperative challenges, and conversion to open surgery. Results: The median age at surgery was 6 years. Intraoperative challenges included dense adhesions (requiring conversion to open surgery in 17% of cases) and vascular injuries, notably two cases involving the right hepatic artery. Managing giant cysts required decompression to improve access. Anatomical anomalies, such as anomalous portal vein positioning, further complicated dissections. Despite these challenges, laparoscopic approaches resulted in favorable outcomes, with a median operative time of 240 min and minimal postoperative complications. Conclusions: Laparoscopic excision of CDCs, while technically demanding, is a feasible and effective approach in experienced hands. Key factors for success include preoperative imaging for detailed anatomical understanding, meticulous dissection, and preparedness for intraoperative complications.